The Prothrombotic Predominance in Metabolic Syndrome: A Complex Patomechanism - Fahmy Rusnanta; Mohammmad Saifur Rohman (Universitas Brawijaya, 2021)
Patients with metabolic syndrome (MS) have many cardiovascular complications related to atherothrombotic complications. MS contributes premature atherosclerosis, increase platelet activation, promote coagulation factors, and reduce fibrinolytic activity. The last step in the atherotrombotic cascade is blood clot formation, and altered clot structure is a key role to determine cardiovascular complications. This review discusses imbalance of hemostasis and eludicate their role of increased propensity to CVD. The correlation of MS and fibrinolysis is reviewed and complex mechanisms that promote coagulation are discussed. Understanding these effects on hemostasis pathway helps to build more effective treatment and preventive strategies to diminish the complication in this condition.